The Practical Application of Oil Painting in the Treatment of Mental Illness - Sun, Xiaoming (Occupational therapy international, 2022)
With the rapid development of economy, politics, science, and technology and the improvement of living material level, people pay more attention to personal physical and mental development. The incidence of mental illness is on the rise. Psychological education curriculum learning and psychological counselling are based on communication; there are still many limitations. The art media enables patients to reveal their subconscious and potential emotional needs, so that interveners have the opportunity to explore these issues and build a bridge of communication with patients. In this paper, oil painting therapy of nonverbal communication is proposed as a way of psychological therapy. The patients in the psychological department of a hospital are served by six stages of therapy, each stage of treatment has different arrangements, and continuous service and treatment are adopted. Based on the art analysis principle of oil painting creation, the therapeutic experience obtained from oil painting creation and the experience gained from oil painting were divided into groups to compare the therapeutic effect and explore the role of oil painting art therapy. The results showed that the scores of the treatment group were significantly lower than those of the control group at 4 weeks and 6 weeks after the art therapy of oil painting creation, showing a significant downward trend overall. Oil painting art therapy may alleviate anxiety, providing data support for the application of oil painting art therapy in patients with depressive episodes.